Perjanjian Perdamaian pada Proses Penundaan Kewajiban Pembayaran Utang Berulang: Kedudukan dan Implikasi - Udin Silalahi; Beatrix Tanjung (Undang: Jurnal Hukum, 2021)
The composition agreement that has been approved or homologated by the commercial court in the process of Suspension of Obligation for Payment of Debt (PKPU), should bind the parties, except for creditors who do not agree to the composition plan. In practice, there are creditors who re-submit a PKPU process, even though there has been a composition agreement, as stated in the decision of the Commercial Court at the Central Jakarta District Court No. 80/Pdt.Sus PKPU/2020/PN.Niaga.Jkt.Pst. Normatively, the law does not prohibit the submission of repeated PKPU applications. In this article will be discussed how is the actual position and legal implication of the composition agreement in the repeated PKPU process, because the composition agreement that has been ratified by the Commercial Court is binding on all creditors; meanwhile, in the recurring PKPU, the Commercial Court issues a new composition agreement. This article concludes, firstly, the composition agreement in the repeated PKPU process remains valid even though the temporary repeated PKPU is granted by the court. Second, the legal consequence of the granting of repeated PKPU, the previous composition agreement remains valid and until the new composition agreement legitimated and the debts of the PKPU Respondent are renewed into the new composition agreement. Abstrak Perjanjian perdamaian yang telah mendapatkan pengesahan atau homologasi pengadilan niaga dalam proses Penundaan Kewajiban Pembayaran Utang (PKPU), seharusnya mengikat para pihak, terkecuali kreditor yang tidak menyetujui rencana perdamaian tersebut. Dalam praktiknya, ada kreditor yang mengajukan ulang suatu proses PKPU, sekalipun telah ada perjanjian perdamaian, sebagaimana pada putusan Pengadilan Niaga pada Pengadilan Negeri Jakarta Pusat No. 80/Pdt.Sus-PKPU/2020/PN.Niaga.Jkt.Pst. Secara normatif, undang-undang tidak melarang pengajuan permohonan PKPU berulang. Dalam artikel ini dibahas, bagaimana sebenarnya kedudukan dan implikasi hukum dari perjanjian perdamaian pada proses PKPU berulang, karena perjanjian perdamaian yang telah disahkan Pengadilan Niaga mengikat kepada semua kreditor, sementara dalam PKPU berulang, Pengadilan Niaga mengeluarkan perjanjian perdamaian baru. Artikel ini menyimpulkan, pertama, perjanjian perdamaian dalam proses PKPU berulang kedudukannya tetap sah walaupun PKPU sementara berulang dikabulkan oleh pengadilan. Kedua, akibat hukum dikabulkannya PKPU berulang, perjanjian perdamaian yang terdahulu tetap sah dan berlaku sampai disahkannya perjanjian perdamaian yang baru dan utang-utang Termohon PKPU berulang diperbarui ke dalam perjanjian perdamaian yang baru.